USE OF LEARNING MANAGEMENT SYSTEMS IN HIGHER EDUCATION: PROGRESS AND POTENTIAL - S. V. BOGOLEPOVA; N. V. MALKOVA (Высшее образование в России)
The article analyzes the possible use of modern learning management systems in the context of Russian tertiary education. It outlines the currents trends in higher education and summarises the experience of LMS use in some European countries and the USA. The focus of the analysis is on the requirements to be met by LMS to correspond to progressive pedagogical ideas, thereby improving the quality of education.